2018
DOI: 10.1016/j.jconrel.2018.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a thermostable spray dried outer membrane vesicle pertussis vaccine for pulmonary immunization

Abstract: Worldwide resurgence of whooping cough calls for improved, next-generation pertussis vaccines that induce broad and long-lasting immunity. A mucosal pertussis vaccine based on outer membrane vesicles (omvPV) is a promising candidate. Further, a vaccine that is stable outside the cold chain would be of substantial advantage for worldwide distribution and application. A vaccine formulated as a powder could both stabilize the vaccine as well as make it suitable for pulmonary vaccination. To that end, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 46 publications
1
20
1
Order By: Relevance
“…Therefore, the current focus for improving pertussis vaccines is on providing longer-lasting immunity, establishing adaptive immune responses against a broader range of antigens to increase the robustness of protection and prevention of transmission by reducing nasal carriage of B. pertussis. www.nature.com/scientificreports www.nature.com/scientificreports/ Earlier we have shown that omvPV induces immune responses against a broad range of antigens, as well as a more Th1/Th17 and less Th2 biased response when administered subcutaneously or in the lungs 13,15,16,21 . In the current study, we compared intranasal and subcutaneous immunization with omvPV from the B1917 strain (summarized in Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the current focus for improving pertussis vaccines is on providing longer-lasting immunity, establishing adaptive immune responses against a broader range of antigens to increase the robustness of protection and prevention of transmission by reducing nasal carriage of B. pertussis. www.nature.com/scientificreports www.nature.com/scientificreports/ Earlier we have shown that omvPV induces immune responses against a broad range of antigens, as well as a more Th1/Th17 and less Th2 biased response when administered subcutaneously or in the lungs 13,15,16,21 . In the current study, we compared intranasal and subcutaneous immunization with omvPV from the B1917 strain (summarized in Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…More research to whether these play a role in longevity of the memory response will be important for future research. www.nature.com/scientificreports www.nature.com/scientificreports/ Previously, we demonstrated that induction of mucosal immunity and faster bacterial clearance from the lungs could be achieved through pulmonary administration of omvPV in both spray dried (reconstituted) and liquid form 15,21 . However, whereas the pulmonary immunization with omvPV led to significant reduction of B. pertussis in the nasal cavity, in the current study we demonstrated that intranasal immunization with omvPV provided complete B. pertussis clearance, also from the nasal cavity of mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This spray significantly improves delivery and decreases the discomfort other intranasal formulations might cause. Importantly, this delivery method still maintains all the outstanding qualities of the classical delivery of these purified outer membrane vesicles (300).…”
Section: Novel Vaccination Strategiesmentioning
confidence: 94%